Evaluasi Buku Teks Bahasa Inggris â€œStairway: A Fun and Easy English Bookâ€ Grade VI Elementary School - Suryarini, Diah Yovita (Trapsila: Jurnal Pendidikan Dasar, 2019)
Choosing a suitable coursebook is not an easy task since coursebook is a key component in most language program. It serves as language input and language practice for learners. It provides the basis for content lesson, the skills taught and the variety of language practice for learner, it also serves as a supplement for teacherâ€™s instruction. The variety of coursebook are available to use by teacher for their classroom. However, teacher need to know the strength and the weakness of the coursebook so that they can choose the best coursebook for their classroom. This study aimed to evaluate coursebook entitled Stairway: A Fun and Easy English Book for sixth grader of Elementary school. The evaluation using the list of criteria of coursebook from Cunningsworth. This study is qualitative descriptive since this study aimed to give the details information about a phenomenon in this case is the coursebook. The result of this study showed that the coursebook entitled Stairway: A Fun and Easy English Book is suitable to use with some adaptation. The result obtained from the suitability from the book with the criteria given. From 44 items of criteria, the book has suitability on 28 criteria or 63% suitability. Accordingly, the book can be used with some adaptation to minimize the weakness in the book. Keywords: ELT Coursebook, Evaluation, Suitability.